Kajian Kritis Al-Ghazali terhadap Pendidikan Islam - Nazwan, Afif Putra; Anjeli, Mardawila Adha; Rahmah, Hafizhatur; Zulmuqim, Zulmuqim; Masyhudi, Fauza (Lembaga Yasin AlSys, 2023)
Education is a necessity for every human being. Therefore, it is necessary for humans to be given a good and quality education. Today, the Western world is recognized as a more advanced and civilized nation. Therefore, the West is considered more capable of providing dynamic and varied new discoveries, as well as technology that makes a significant contribution to science. So that many parts of the world are oriented towards the West, especially regarding the development of science. As a result, many generations of Muslims are no longer aware of the Islamic figures who greatly influenced the progress of the world of education, so it is important to reintroduce Islamic figures who have a great influence on the progress of education. Among them is Imam Al-Ghazali. In today's modern era, it is very necessary to know Islamic figures who make a major contribution to the progress of the world of education. So that people do not forget Islamic figures who are basically able to influence and develop education in the Islamic world. Therefore, this article will discuss